4 A 6-year retrospective review of injuries sustained during the singapore cricket club international rugby sevens tournament. (December 2018) - Xu, C; Walter, J; Low, LL; Lai, KW
Abstract : Rugby Sevens is gaining popularity in Asia as evidenced by the increase in number of tournaments and participants of the sport. Currently, there are limited studies that look at injury statistics for Rugby Sevens, especially at the amateur level. This study aims to assess injury patterns among amateur Rugby Sevens players participating in the annual Singapore Cricket Club Rugby Sevens International tournament from 2012 to 2017. A retrospective review was made of recorded injury data of all players participating in the 2012 to 2017 Singapore Cricket Club Rugby Sevens Internationals tournament. Main outcome measures include incidence rate of injuries expressed per 1000 player hours, injury rate according to anatomical location, and comparative injury incidence between successive days within each tournament. 343 injuries were recorded over the 6 tournaments, with an injury incidence of 348 per 1000 player hours. The lower limb was the most commonly injured region (46%, 159 per 1000 paying hours), followed by head and neck injuries (24%, 82 per 1000 playing hours), upper limb injuries (21%, 74 per 1000 playing hours) and trunk injuries (9%, 32 per 1000 playing hours). There was a greater incidence of injuries on day 3 of competition compared to day 1 for the 2013 and 2016 tournaments (2013: 541 per 1000 player hours vs. 520 per 1000 player hours; 2016: 191 per 1000 player hours vs. 767 per 1000 player hours). Being the first study of injuries in Asian Rugby Sevens, this serves to inform of the background risk of injuries, which is much higher than is currently reported in the literature. A well-designed, prospective injury surveillance study will be necessary to investigate if injury rates are indeed higher at the amateur level in Asia, and whether there are modifiable risk factors unique to this part of the world which should be considered to guide injury prevention programmes.